Self-assembly cloning: a rapid construction method for recombinant molecules from multiple fragments - Akira Matsumoto; Taichi Q. Itoh (BioTechniques)
Enzyme-free cloning (EFC) can rapidly produce an in-frame fusion gene with multiple fragments. To practically apply EFC, we investigated the extent and sequence of complementary staggered overhangs necessary to direct self-assembly of multiple fragments as well as a size limitation of the constructed DNA molecule. Six-base pair overhangs with 50% GC content were sufficient to direct self-assembly. A functional plasmid that exceeded 10 kb, which includes an in-frame fusion domain, was efficiently constructed from four PCR fragments in one step by our improved method.